Implementación de una aplicación web para la gestión y análisis de datos del consumo de agua potable de los clientes de la parroquia Pucayacu centro. - Saltos Intriago, Genesis Yajaira (2023)
The main objective of this research project was to implement a web application that allows the management and analysis of drinking water consumption data for efficient decision-making. In this regard, during this development, an agile Scrum methodology was used, which allows working together with the beneficiaries and the development team. In this way, it is possible to generate an application that fulfills the users’ perspectives due to its functionality. In addition, software development tools with free licensing have been used, such as the PHP programming language, and MariaDB database. As a result, a fully functional web application was obtained where the administrator can access through internet to manage users, sectors, rates, associate members, meters, and monthly consumption, in the same way, the software owns a significant technological impact by improving operational efficiency, providing easy access to information, enable data-based decision making, promote transparency and citizen participation, and ensure data security. Consequently, types of research, research techniques, and research methods have been used, which have allowed a simple and efficient creation of the project. Finally, it can be concluded that it is important to carry out a bibliographical investigation, choose appropriate tools, and methodologies, establish clear requirements, and carry out exhaustive tests. Similarly, for the investigation different reliable bibliographic sources were identified for the selection of tools and methodologies according to the needs, establishing a solid development process, and carrying out usability tests.